2022
DOI: 10.1007/s10566-022-09701-0
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Psychoactive Substance Use During the First COVID-19 Lockdown: A Cross Sectional Study in Italy

Abstract: Background Italy was one of the first European countries to be affected by Covid-19. Due to the severity of the pandemic, the Italian government imposed a nationwide lockdown which had a great impact on the population, especially adolescents. Distance-learning, moving restrictions and pandemic-related concerns, resulted in a particularly stressful situation. Objective This cross-sectional study aims to analyse substance consumption and its associated facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…The important findings of our study are related to substance use and data confirmed by studies conducted during the lockdown (Biagioni et al, 2023). Significant differences emerged among the three groups of participants (students, teachers, and parents) regarding substance use.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The important findings of our study are related to substance use and data confirmed by studies conducted during the lockdown (Biagioni et al, 2023). Significant differences emerged among the three groups of participants (students, teachers, and parents) regarding substance use.…”
Section: Discussionsupporting
confidence: 88%
“…Approximately one in three students who had never used substances reported using them more frequently (Brener et al, 2022; Chaiton et al, 2022). Italian students drank alcohol (43.1%); 4.2% became intoxicated, 16% engaged in binge drinking by consuming five or more drinks in a row, 18.4% smoked at least one cigarette, 5.9% used cannabis, and 0.9% used at least one illegal substance (Biagioni et al, 2023). Studies in this regard are contradictory: the results of other surveys suggest that the prevalence of substance use declined (Zolopa et al, 2022) because the availability of and access to them was limited (Layman et al, 2022), with students forced to stay at home.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chaiton et al (2022), the largest increases were observed in the consumption of alcohol (+19%), cigarettes (+16%), e‐cigarettes (+37%), and cannabis (+47%). In regard to the prevalence of psychoactive substance consumption among youths during Italy's lockdown period, an estimated 43.1% of students drank alcohol, 4.2% became intoxicated, and 16% engaged in binge drinking characterized by having five or more drinks in a row; 18.4% reported smoked at least one cigarette; 5.9% used cannabis; and 0.9% reported using at least one illegal substance (Biagioni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Youth who are victims of bullying have been shown to exhibit a number of important social deficits, including low levels of social acceptance, poor friend and peer support, inadequate social skills and social assertiveness, and greater loneliness [13][14][15]. Victims also have poorer school attendance and academic achievement [16,17] and are at greater risk of depressive symptoms and anxiety [18][19][20]. Several studies have shown that bullying behavior and substance use often co-occur in the same individuals [21][22][23], although the rates vary as a function of bullying roles.…”
Section: Introductionmentioning
confidence: 99%